Geology of the Late Carboniferous, Permian and Early Triassic basins of the Eastern Pyrenees - Josep Gisbert; Ana Simón-Muzás; Antonio Casas-Sainz; Ruth Soto (Journal of Maps)
We present a detailed geological map of the Upper Carboniferous, Permian and Triassic rocks of the southern border of the Axial Zone in the Eastern Pyrenees. These units were deposited in three intra-mountain, terrestrial basins, characterized by the emplacement/deposition of volcanic, sub-volcanic and volcaniclastic units (ca. 1000 m thick) together with continental red beds. The map is based on unpublished drafts, sketches and structural data. This previous information was complemented with new structural, petrologic and stratigraphic data. The geological map is presented together with three cross-sections, a detailed lithological description, and a stratigraphic correlation panel to help understand the stratigraphy, volcanism and structure and, ultimately, the geometry and origin of the highly subsident areas of this segment of the chain in post-Variscan times. The geological map gives new clues for reconstructing the geometry of these basins and the distribution of the volcanic episodes during the Late Carboniferous and Permian.